2008
DOI: 10.1165/rcmb.2007-0249oc
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Asbestos-Induced Lung Inflammation and Fibrosis after Radiation and Bone Marrow Transplant

Abstract: The effect of lung irradiation on subsequent inflammatory or fibrotic lung injuries remains poorly understood. We postulated that irradiation and bone marrow transplantation might impact the development and progression of lung remodeling resulting from asbestos inhalation. Our objective was to determine whether irradiation and bone marrow transplantation affected inflammation and fibrosis associated with inhaled asbestos exposure. Inflammation, cytokine production, and fibrosis were assessed in lungs of naïve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…However, BMDC therapy minimized the levels of IL-1β and IL-1R1 mRNA (Fig. 5A,B) in concordance with Ortiz et al [9] and Levis et al [20], who observed a downregulation of both after infusion of BMDCs in experimental lung fibrosis. The high levels of IL-1RN induced after BMDC therapy (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…However, BMDC therapy minimized the levels of IL-1β and IL-1R1 mRNA (Fig. 5A,B) in concordance with Ortiz et al [9] and Levis et al [20], who observed a downregulation of both after infusion of BMDCs in experimental lung fibrosis. The high levels of IL-1RN induced after BMDC therapy (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Because we know so much about the fundamental details of this model (17,18), it offers an outstanding opportunity to learn a great deal about what stem cells can do as the lesions develop. In a similar study (19), investigators in Vermont suggested that a bone marrow transplant could ameliorate the fibrogenic effects of asbestos exposure.…”
Section: Experimental Modelsmentioning
confidence: 97%
“…The bulk of the evidence suggests that MSCs migrating to lesions produce favorable results, such as in ameliorating fibrogenesis caused by bleomycin (4), radiation and inhaled asbestos (19), and reducing inflammation and mortality in a model of acute lung injury as discussed above (10). In an elegant study from Ortiz's laboratory (4), it was shown that MSCs block production of TNF-a and IL-1 that apparently mediate bleomycin-induced lung injury.…”
Section: Experimental Modelsmentioning
confidence: 99%
“…Using transgenic (Tg) mice expressing an inhibitory κ B (I κ B) mutant resistant to phosphorylation-induced degradation and targeted to the bronchiolar epithelium via the CC10 promoter in a murine model of asbestosis, Tg(+) mice exposed to asbestos had less BALF inflammatory cytokine levels (eg, KC, IL-6, and IL-1 β ) and reduced levels of bronchiolar and distal epithelial proliferation as compared with Tg(−) mice 96. Two groups have recently shown that bone marrow progenitor cells contribute to the inflammatory and fibrogenic effects of asbestos 97,98. These studies underscore the importance of TNF- α , the NF- κ B–dependent pathway, and bone marrow progenitor cells in the pathogenesis of asbestos-induced lung disease that may lead to novel therapeutic strategies.…”
Section: Pathophysiology—what’s New?mentioning
confidence: 99%